Importance of Implementing Physical Education Since Childhood and Its Scope - LIU, GENPING; Fernando, Yudi (PT. BERBAGI TEKNOLOGI SEMESTA, 2023)
Children's health issues have always been a focus of concern for schools, families, and society. Unfortunately, children are currently facing some potential health threats. For example, obesity caused by imbalanced diet and high calorie diet, sedentary behaviour caused by spending too much time in front of mobile phones or computer screens, and immune decline caused by insufficient physical activity. This study analysed the impact and scope of physical education activities on children and found that physical activities can improve overall quality of life by promoting a healthy lifestyle. Physical activities can help improve muscle strength and protect bones from fractures. Research has found that people engaged in physical education are healthier and more likely to break unhealthy eating habits than others. The importance of physical education is also reflected in its ability to cultivate children's cognitive abilities and improve their personality. It is recommended that schools, society, and families collaborate to promote children's comprehensive development and healthy growth through physical education.